DETERMINANTS FACTORS OF ISLAMIC SOCIAL REPORTING IN INDONESIAN SHARIA BANKS FOR THE 2020-2023 PERIOD - Aditya, Rifky; Arifin, Mohammad Rahmawan (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research seeks to examine the determinants affecting the Islamic Social Reporting of Islamic Commercial Banks from 2020 to 2023. The independent factors include firm size, company age, profitability, and the size of the sharia supervisory board. This research used a purposive sampling strategy, using 10 Indonesian Islamic Commercial Banks as samples. The used analytical technique is panel data regression using EViews 13 software. The findings indicated that both firm size and the size of the sharia supervisory board have a favorable and significant influence on ISR. The company’s age and profitability have no significant influence on ISR